Permeability of Bituminous Coal to CH4 and CO2 Under Fixed Volume and Fixed Stress Boundary Conditions: Effects of Sorption - Liu, Jinfeng; Spiers, Christopher J. (Frontiers in Earth Science, 2022)
Permeability evolution in coal reservoirs during CO2-Enhanced Coalbed Methane (ECBM) production is strongly influenced by swelling/shrinkage effects related to sorption and desorption of CO2 and CH4, respectively. Numerous permeability models, coupling the swelling response of coal to gas sorption, have been developed to predict in-situ coal seam permeability evolution during (E)CBM. However, experimental studies, aimed at testing such models, have mainly focused on the permeability changes occurring under constant lateral stress conditions, which are inconsistent with the in-situ boundary condition of (near) zero lateral strain and hence evolving lateral stresses. In addition, recent research demonstrates fully coupled stress-strain-sorption-diffusion behaviour in cleat-free coal matrix material exposed to sorbing gas. It is unclear how such effects influence permeability evolution and whether a simple fracture permeability model, such as the Walsh elastic asperity loading model, is appropriate. In this study, we performed permeability measurements to CH4 and CO2, using the steady-state method, on a cylindrical sample of high volatile bituminous coal (25mm in diameter) with a clearly visible cleat system, under (near) fixed volume versus fixed stress conditions. To isolate the effect of sorption on permeability evolution, helium (non-sorbing gas) was used as a control fluid. All flow-through tests reported here were conducted under conditions of single-phase flow at 40℃, employing Terzaghi effective stresses of 14-35MPa. Permeability evolution versus effective stresses was obtained under both fixed volume and fixed stress conditions, showing an exponential correlation. Importantly, permeability (κ) obtained at similar effective stresses showed κ_helium > κ_(CH_4 ) >> κ_(CO_2 ), and κ measured at fixed volume is higher than fixed stress. This all demonstrates that permeability to CH4 and CO2, under in-situ boundary conditions, is strongly influenced by the coupled effects of a) self-stress generated by swelling, b) the change in effective stress coefficient upon sorption, c) sorption-induced closure of transport paths independently of poro-elastic effect, and d) heterogeneous gas penetration and equilibration, dependent on diffusion. Our results also show that the Walsh permeability model offers a promising basis for relating permeability evolution to in-situ stress evolution, using appropriate parameter values corrected for the effects of stress-strain-sorption-diffusion.